2014
DOI: 10.3382/ps.2014-04156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of source and level of glycerin in the diet on growth performance, liver characteristics, and nutrient digestibility in broilers from hatching to 21 days of age

Abstract: The influence of source and level of inclusion of raw glycerin (GLYC) in the diet on growth performance, digestive traits, total tract apparent retention (TTAR), and apparent ileal digestibility of nutrients was studied in broilers from 1 to 21 d of age. There was a control diet based on corn and soybean meal and 8 additional diets that formed a 2 × 4 factorial with 2 sources of GLYC and 4 levels of inclusion (2.5, 5.0, 7.5, and 10%). The GLYC used were obtained from the same original batch of soy oil that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
1
14
0
3
Order By: Relevance
“…In addition, consistent with studies evaluating the addition of increasing glycerin levels (up to 10%) in broiler diets (Zavarize et al, 2012;Menten et al, 2008;Fernandes et al, 2010), no negative effect of the inclusion of up to 8% of glycerin was detected on broiler performance, suggesting that glycerin can be included in broiler diets, provided its chemical composition. Mandalawi et al 2014 showed that raw glycerin from the biodiesel industry can be used efficiently, up to 10% of the diet, as a source of energy for broilers from 1 to 21 days of age and that the energy content of well-processed raw glycerin depends primarily on its glycerol content. However, when high glycerin levels were added to the diet (20 and 25%), Simon et al (1997) performance impairment was observed.…”
Section: Evaluation Of Dietary Glycerin Inclusion During Different Brmentioning
confidence: 99%
“…In addition, consistent with studies evaluating the addition of increasing glycerin levels (up to 10%) in broiler diets (Zavarize et al, 2012;Menten et al, 2008;Fernandes et al, 2010), no negative effect of the inclusion of up to 8% of glycerin was detected on broiler performance, suggesting that glycerin can be included in broiler diets, provided its chemical composition. Mandalawi et al 2014 showed that raw glycerin from the biodiesel industry can be used efficiently, up to 10% of the diet, as a source of energy for broilers from 1 to 21 days of age and that the energy content of well-processed raw glycerin depends primarily on its glycerol content. However, when high glycerin levels were added to the diet (20 and 25%), Simon et al (1997) performance impairment was observed.…”
Section: Evaluation Of Dietary Glycerin Inclusion During Different Brmentioning
confidence: 99%
“…Results of the present study are in line with the findings of Bernardino et al (2015) who noticed that including crude glycerine in diets improved FCR in broilers and concluded that this was due to the low concentration of methanol (20.62 mg · l −1 ) in glycerine preparation. Furthermore, Mandalawi et al (2014) stated that FCR improved with glycerine addition in broiler diets from 1 to 21 day of age. Contradictive results were obtained by Cerrate et al (2006) who demonstrated that glycerine had no impact on FCR in poultry.…”
Section: Growth Performancementioning
confidence: 99%
“…Moreover, higher levels of glycerine (12 and 15%) resulted in lower weight gains, and increasing crude glycerine level quadratically increased feed intake at 10 days of age. Mandalawi et al (2014) investigated the effects of different glycerine sources and levels in broiler diets. A 2×2 factorial design was used with four levels of inclusion (2.5, 5, 7.5 and 10%), along with two sources of glycerine.…”
Section: Introductionmentioning
confidence: 99%
“…Raw glycerin, a coproduct of the ethanol industry, is an attractive energy source that can replace part of the cereal grain in poultry diets and contribute to reduce feed cost (Lammers et al, 2008;Swiatkiewicz and Koreleski, 2009;Mandalawi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum level of inclusion of GLYC in laying hen diets for optimal production, has been estimated within the range of 50 to 100 g/kg (Lammers et al, 2008;Swiatkiewicz and Koreleski, 2009;Németh et al, 2013). Also, the inclusion of GLYC in broiler diets increased dry matter (DM) and gross energy (GE) retention (Kim et al, 2013;Mandalawi et al, 2014). In spite of the commercial interest for using GLYC as an energy source in the diet, little information is available on the effects of GLYC on total tract apparent retention (TTAR) of dietary components and egg quality in laying hens.…”
Section: Introductionmentioning
confidence: 99%